A Transaction Cost Framework in Supply Chain Relationships: A Social Capital Perspective. Issue 1 (2nd April 2016) - Kanwal, Aneela; Rajput, Amer
ABSTRACT: Fostering strong and collaborative buyer–supplier relationships is essential for enhancing supply chain performance. Therefore, buyers and suppliers both attempt to develop collaborative relationships. Sometimes these collaborative activities do not result in a happy ending, and consequently, are harmful in the form of opportunism on the part of the buyer or supplier. Opportunism has remained significant in buyer–supplier studies. However, there is a lack of research on opportunism, behavioral uncertainty, and relationship-specific investments from the perspective of social capital factors in an industrial marketing setting. The primary aim of the current study is to identify the role of social capital and transaction cost theory variables. This study integrates different research on transaction cost theory variables and also reviews the relationship of these variables to social capital factors. The current study includes 83 studies from various journal article databases such as Wiley-Blackwell, Emerald, SpringerLink, Taylor & Francis, JSTOR, and ScienceDirect. This review focuses on the most recent studies. This study identifies various perspectives regarding the effect of social capital on transaction cost variables. Conclusions and implications for managers are also discussed.